A country case study comparison on groundwater and surface water interaction. (25th October 2011) - Eslamian, Saeid; Karimi, Sara Shaeri; Eslamian, Faezeh
Traditionally, managing water resources has focused on surface water or groundwater as if they were separate entities. As development of land and water resources increases, it is apparent that development of either these resources affects the quantity and quality of the other. Nearly all surface water features interact with groundwater. These interactions take many forms. This paper provides an overview of the case studies and methods that are currently applied and described in the literature for estimating fluxes at the groundwater?surface water interface. Suggestions for performing further case studies in different climates are finally presented.